EFFECT OF USING L-ASPARAGINASE IN REDUCING ACRYLAMIDE PERCENTAGE IN BISICUT - & et al., Jebur (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was aimed to know the efficiency of partially purified L- asparaginase produced from local isolate from Erwinia spp. to reduce the percentage of acrylamide formed in Biscuit. Four types of biscuit from wheat flour were prepared (T1, T2, T3, T4),and T1 as control. High performance liquid chromatography technique was used to estimate acrylamide ratio in biscuit , Effect of enzyme addition  on flour chemical and rheological properties was studied, also dough behavior ,gluten percentage, water absorption and amylase enzyme activity was estimated. The results revealed  that  the  addition of  experimental asparaginase ( specific activity 20.5 unite mg-1 ) with 1% of flour weight lead to reduce in acrylamide formation in Biscuit  to 89 %  compared  to  control sample ( in absence of enzyme ) . Moreover, the addition of Asparagine to flour at 0.1 % of its weight, where L- asparaginase was available caused a negative effect on enzyme efficiency in reducing the acrylamide in biscuit. So the level of acrylamide was reduced to 57.7 %. In the other hand , the percentage of acryl amide in biscuit was increased to   233 % when the asparagine was added to mixture in absence of L- asparaginase .Addition of  the enzyme to flour have no effect on the percentage value of gluten but improved the  stability of dough .The  enzyme  addition also led to increase amylases activities.  Addition of experimental enzyme had no effect on quality and sensory evaluation of biscuit.